1994
DOI: 10.1183/09031936.94.07122199
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal lung function study in heterozygous PiMZ phenotype subjects

Abstract: L Lo on ng gi it tu ud di in na al l l lu un ng g f fu un nc ct ti io on n s st tu ud dy y i in n h he et te er ro oz zy yg go ou us s P Pi iM MZ Z p ph he en no ot ty yp pe e s su ub bj je ec ct ts s Total lung capacity and residual volume increased, whereas forced expiratory volume in one second, expiratory flows, diffusing capacity of the lungs for carbon monoxide, and static transpulmonary pressures decreased in the PiMZ patients. The majority of the controlled functional parameters were found to deteriora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…In a prospective cohort that followed iron-ore miners for 5 years, MZ individuals had more decline in FEV1/FVC than MM ones, but there was no difference in respiratory symptoms [61]. In another 10-year longitudinal study among a cohort of nonsmokers matched for age, height and body weight, pulmonary elasticity was measured and was found to decrease significantly over time in the MZ group when compared to the MM group [62]. In smokers there was a significant difference in FEV1, with annual decline of 75 mL in MZ versus 53 mL in MM subjects [63].…”
Section: Progression Of Obstructive Lung Disease In Mz Individualsmentioning
confidence: 94%
“…In a prospective cohort that followed iron-ore miners for 5 years, MZ individuals had more decline in FEV1/FVC than MM ones, but there was no difference in respiratory symptoms [61]. In another 10-year longitudinal study among a cohort of nonsmokers matched for age, height and body weight, pulmonary elasticity was measured and was found to decrease significantly over time in the MZ group when compared to the MM group [62]. In smokers there was a significant difference in FEV1, with annual decline of 75 mL in MZ versus 53 mL in MM subjects [63].…”
Section: Progression Of Obstructive Lung Disease In Mz Individualsmentioning
confidence: 94%
“…However, because the low prevalence of the relevant AAT variants, the proportion of COPD attributable to this gene was only y1%. A few studies assessing the association between different genotypes and the development of COPD suggested that those with an MZ genotype could be at higher risk of COPD than those with an MM genotype [69,70]. Other recent findings include studies showing an association between the presence of deoxyribonucleic acid (DNA) instability and COPD in smokers [71] and a higher frequency of the glutathione S-transferase (GSTP1) polymorphism in patients with COPD [72].…”
Section: Genetic Determinantsmentioning
confidence: 98%
“…Heterozygous, PiMZ individuals have moderately reduced serum levels A1AT, but whether they have increased risk of COPD is uncertain. Tarjan et al (Tarjan et al, 1994) in longitudinal lung function study in heterozygous PiMZ subjects observed a decrease in elasticity and deterioration lung function parameters in comparison to those without A1ATD, which supports the concept of PiMZ phenotype being a risk factor for pulmonary emphysema development at a younger age. Dahl et al (Dahl et al, 2002) found that PiMZ heterozygotes had a slightly greater rate of decrease in FEV 1 .…”
Section: Hereditary Alpha-1-antitrypsin Deficiency and Emphysemamentioning
confidence: 59%